Galectin-3 reflects mitral annular plane systolic excursion being assessed by cardiovascular magnetic resonance imaging - Kim, Seung‑Hyun; Behnes, Michael; Natale, Michèle; Hoffmann, Julia; Reckord, Nadine; Hoffmann, Ursula; Budjan, Johannes; Henzler, Thomas; Papavassiliu, Theano; Borggrefe, Martin; Akın, Ibrahim (Disease markers, 2016)
Background. This study investigates whether serum levels of galectin-3 may reflect impaired mitral annular plane systolic excursion (MAPSE) in patients undergoing cardiac magnetic resonance imaging (cMRI). Methods. Patients undergoing cMRI during routine clinical care were included prospectively within an all-comers design. Blood samples for biomarker measurements were collected within 24 hours following cMRI. Statistical analyses were performed in all patients and in three subgroups according to MAPSE (MAPSE I: ≥11 mm, MAPSE II: ≥8 mm-<11 mm, and MAPSE III: <8 mm). Patients with right ventricular dysfunction (<50%) were excluded. Results. 84 patients were included in the study. Median LVEF was 59% (IQR 51-64%). Galectin-3 correlated significantly with NT-proBNP (, ). Galectin-3 increased significantly according to the different stages of impaired MAPSE () and was able to discriminate both patients with impaired MAPSE <11 mm (area under the curve (AUC) = 0.645, ) and <8 mm (AUC = 0.733, ). Combining galectin-3 with NT-proBNP improved discrimination of MAPSE <8 mm (AUC 0.803, ). In multivariable logistic regression models galectin-3 was still associated with impaired MAPSE (MAPSE < 11 mm: odds ratio (OR) = 3.53, ; MAPSE < 8 mm: OR = 3.18, ). Conclusions. Galectin-3 reflects MAPSE being assessed by cardiac MRI.